Fracture Toughness and Microstructure of Gas Metal Arc Welded Plates of Aluminium Alloy 5083 Using Different Filler Wires and Heat Inputs. Issue 1 (September 2020) - Hidayat, Arif; Junaidi, Arif; Mudiantoro, Sunoto; Winarto, Winarto
Abstract: Aluminum alloys AA5083 is alloys which mostly used in the hull components of the ship and high-speed craft. Commonly gas metal arc welding (GMAW) is used for joining the construction. Welding strength especially cracks toughness, is very important on this welding due to the regular operation of the ship or high-speed craft. In this research, welding of aluminum alloys AA5083 with dimension 150 mm x 350 mm and thickness 15 mm and 20 mm, were carried out by gas metal arc welding using two difference filler metal ER5183 and ER5356, and 99% argon is used as shielding gas. The result of the experiment that the maximum value of excellent toughness was shown on welding with thickness plate 15 mm using filler metal ER5356 and heat input 7.8 kJ/cm.